Geometric modeling of 3D fractal objects - Kyaw Win Aung; Bohez, Erik L.J.; Huynh, Ngoc Phien; Zhao, Ming; The Government of Australia (Bangkok : Asian Institute of Technology, 1991)
The purpose of this study is to develop a technique for modeling three-dimensional real objects using fractals and to study the Collage theorem and the Box counting theorem. This study comprises two parts. The first part of the work is based on Iterated Function Systems (IFS) and the usefulness of the Collage theorem in finding the IFS codes is shown. The second part is based on the random fractal surface method with the atjomalies removal. The fractal dimension of the object can be determined by using the Box counting theorem for both parts. Moreover, the actual data storage and the rendering time can be reduced by using fractals.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1991
Keywords: Fractals